Utilising carbon dioxide for transport fuels: The economic and environmental sustainability of different Fischer-Tropsch process designs. (1st November 2019) - Cuéllar-Franca, Rosa; García-Gutiérrez, Pelayo; Dimitriou, Ioanna; Elder, Rachael H.; Allen, Ray W.K.; Azapagic, Adisa
Graphical abstract: Highlights: For large-scale plants, CO2 -derived fuels outperform diesel environmentally. The exceptions are global warming and ozone depletion which are lower for diesel. Optimising the systems reduces global warming of CO2 fuels by 70% below diesel. CO2 fuels are not economically viable, costing ∼4 times more than fossil diesel. Optimising process yields would allow decreasing the subsidies to 8%. Abstract: Producing fuels and chemicals from carbon dioxide (CO2 ) could reduce our dependence on fossil resources and help towards climate change mitigation. This study evaluates the sustainability of utilising CO2 for production of transportation fuels. The CO2 feedstock is sourced from anaerobic digestion of sewage sludge and the fuels are produced in the Fischer-Tropsch (FT) process. Using life cycle assessment, life cycle costing and profitability analysis, the study considers four different process designs and a range of plant capacities to explore the effect of the economies of scale. For large-scale plants (1, 670 t/day), the FT fuels outperform fossil diesel in all environmental impacts across all the designs, with several impacts being net-negative. The only exceptions are ozone depletion, for which fossil diesel is the best option, and global warming potential (GWP), which is lower for fossil diesel for some process designs. Optimising the systems reduces the GWP of FT fuels in the best case by 70% below that of fossil diesel. Assuming a replacement of 9.75–12.4% of fossil diesel consumed in the UK by 2, 032, as stipulated by policy, would avoid 2–8 Mt of CO2 eq./yr, equivalent to 2–8% of annual emissions from transportation. However, these fuels are not economically viable and matching diesel pump price would require subsidies of 35–79% per litre. Optimising production yields would allow decreasing the subsidies to 8%. Future research should be aimed at technology improvements to optimise these systems as well as evaluating different policy mechanisms needed to stimulate markets for CO2 -derived fuels.